The History of Christianity in the Southern Part of Ondo State. 1875- 1981. - Akinwumi, Moses Olagoke (Obafemi Awolowo University, 2014)
The focus of this work is the history of Christianity in the Southern part of Ondo State between 1875 and 1981. But before the advent of Christianity, the indigenes of the area were adherents of African Traditional Religion end still today, Traditional Religion is practiced, The White Missionaries brought Christianity to this area in the year 1875. The C.M.S missionaries were the first to visit the area and they were later followed by other Missionaries from the Catholic and the Methodist Churches. After some of the Missionaries had gained ground the area, the indigenous and. Pentecostal (Aladura) churches came into being.